Effect of sublethal doses of some insecticides and their role on detoxication enzymes and protein-content of Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) - Seham Mansour Ismail (Bulletin of the National Research Centre, 2020)
Abstract Background The indiscriminating and intensive use of insecticides to control the cotton leafworm (CLW), Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae), usually induces high levels of resistance. The insecticides are the principal method for controlling this pest because of its critical role in reducing insects when the economic threshold (ETL); therefore, the effectiveness of these insecticides should be maintained. So, the target of the present work was directed to focus on studying the change in the activities of some important enzymes as a result of sublethal treatment concentrations (viz. LC25 values) of tested new insecticides (profenofos, cyfluthrin, emamectin benzoate, lufenuron, and spinetoram). The expected results could offer better understanding and more specific information about the resistance development in field populations of CLW because resistance is a significant challenge to pest control workers and these results may contribute to making the right decision at the right time. Materials and methods Bioassays were performed on fourth instar larvae of S. littoralis field populations compared with the laboratory strain to assess the activity of the emamectin benzoate, lufenuron, and spinetoram by LC25 and study the biochemical activities of some detoxification enzymes, like acetylcholinesterase (AChE), glutathione S-transferases (GST), alkaline phosphatase (ALP), and acid phosphatase (ACP) in fourth larval instar which was treated with LC25; protein content is also determined. Results The emamectin benzoate was the most toxic compound followed by lufenuron, cyfluthrin, spinetoram, and profenofos with the corresponding LC50 values of 0.05, 49.18, 70.99, 130.26, and 156.78 ppm respectively. The results showed that all the tested insecticides at LC25 value gave a slight inhibition of the acetylcholinesterase (AChE) activity, except profenofos was the most potent one. The activity of glutathione S-transferase (GST) of larvae treated with spinetoram has significantly increased, whereas the enzyme activity was significantly inhibited following cyfluthrin and non-significantly inhibited following profenofos, lufenuron, and emamectin benzoate application. There were no significant differences between treated and untreated larvae in ACP activity. In contrast, the alkaline phosphatase (ALP) activity of larvae treated with tested insecticides significantly increased, while the activity was inhibited following cyfluthrin application. On the other hand, spinetoram, emamectin benzoate, and lufenuron exhibited significant increment in the protein content, whereas there was no significant effect following either cyfluthrin or profenofos treatments. Conclusions In summary, the present results suggest that not only the lethal effects but also the sublethal effects of newly tested insecticides could have a negative influence on the dynamics of CLW; thus, these sublethal effects can be integrated into pest control to reduce the overuse and misuse of insecticides. This effect appears reduction in the activity of detoxification enzymes, resulting in response to the tested insecticide by the lowest concentration of (sublethal doses). Also, the inhibition of detoxification enzymes, which represents defensive reactions in insects, is playing important role in reducing resistance in S. littoralis, which is one of the most dangerous pests of all agricultural crops in the world. Therefore, these results were valuable for the practical use of these insecticides in IPM programs.